Artificial Urinary Sphincter Cuff Downsizing Improves Continence and Patient Satisfaction in Cases of Sub-cuff Atrophy. Issue 4 (30th April 2023) - Krughoff, Kevin; Nosé, Brent D.; Peterson, Andrew C.
Abstract : Purpose: The management of artificial urinary sphincter sub-cuff atrophy remains controversial, and clinical outcomes are underreported. We intend to examine the impact of cuff downsizing in cases of isolated sub-cuff atrophy. Materials and Methods: We reviewed our prospectively collected, institutionally approved quality improvement database for this study from 2011 to 2022. Institutional Review Board approval was obtained for the analysis. Sub-cuff atrophy in patients with post-prostatectomy incontinence was diagnosed with a clinical presentation of recurrent urinary leakage, serial pelvic films, cystoscopy, and patient evaluation. Outcomes were assessed with pad use, subjective measures, and American Urological Association Symptom Score scores. Results: During the study interval, 871 encounters for artificial urinary sphincter placement were identified, 229 for revision or replacement, of which cuff downsizing for isolated cases of sub-cuff atrophy occurred in 34. Downsizing took place after a median of 6.5 years after initial artificial urinary sphincter placement. Of the patients, 97% reported subjective improvement and 93% experienced a decrease in daily incontinence pad use, with a mean±SD decrease of 2.2±1.45 pads ( P < .01). American Urological Association Symptom Score bother scores decreased from pre-downsizing values by a mean±SD of 1.5±1.4 ( P = .01). After a median follow-up of 1.8 years after downsizing, 24 (70.6%) of downsized cuffs remained in place, 2 (5.9%) were further downsized, 2 (5.9%) required replacement for mechanical failure, 4 (11.8%) underwent removal for erosion, and 2 (5.9%) underwent replacement for a herniated pressure regulating balloon. Conclusions: When diagnosed using objective criteria, cuff downsizing improves continence and patient satisfaction in cases of sub-cuff atrophy.